Effects of cropland-to-orchard conversion on soil multifunctionality, particularly nitrogen cycling in the eastern Loess Plateau - Fan, Zhuanzhuan; Wang, Jiali; Lv, Dandan; Li, Shangbin; Miao, Yuan; Hu, Mengjun; Wu, Donghui; Liu, Fengying; Wang, Dong (Frontiers in Microbiology, 2024)
The conversion of cropland to orchards is one of the main measures of the Grain for Green Program for soil and water conservation and ecosystem function maintenance in the eastern Loess Plateau, China. However, the patterns and influencing forces of soil multifunctionality during the conversion from cropland to orchard remain unclear. This study evaluated the responses and regulating factors of soil multifunctionality following the conversion of cropland to pomegranate (Punica granatum L.) orchard along a 10-year chronosequence. Results showed that the conversion of cropland to pomegranate trees significantly increased the L-leucine aminopeptidase enzyme activity from 4.77 to 17.69 nmol g -1 h -1 . The 10-year pomegranate stand exhibited the highest nitrogen (N) cycle multifunctionality. The N cycle multifunctionality was positively correlated with soil dissolved organic carbon (C) content, soil available phosphorus content, microbial biomass C content, phospholipid fatty acid, and soil feature index (All p < 0.05). Structural equation modeling suggested that the increased N cycle multifunctionality was attributed to soil feature index rather than soil microbial C content and phospholipid fatty acid.Land-use change did not affect soil C cycle, phosphorus cycle, or soil multifunctionality. Overall, our findings reveal that cropland conversion to orchards significantly enhances soil N cycle multifunctionality, highlighting the soil feature index's role in maintaining soil function. The conversion from cropland to orchards, which has economic benefits and increases soil N cycle multifunctionality, is an effective approach of the Grain for Green Program in the Loess Plateau.